Crisis leadership in SMEs and the response to COVID-19. An exploratory case study of South Korean SMEs. - Kim, Bora (2020)
The recent outbreak of COVID-19 has been disrupting SMEs (Small-medium sized enterprise) in particular. In a crisis such as COVID-19, leadership has been considered as most important in SMEs, but prior studies showed less emphasis on it. Specifically, there is only a limited amount of research on crisis leadership in SMEs in East Asia. The dissertation explores how South Korean SMEs establish crisis leadership to respond to the impact of the COVID-19. By investigating Korean SMEs, the dissertation attempts to address both leadership in SMEs to respond to COVID-19 and crisis leadership in South Korean SMEs. By interviewing five Korean SMEs owners-senior managers, the dissertation explores the impact of the COVID-19 and their crisis leadership; crisis leadership type and crisis leadership competencies. Our findings reveal that the unique leadership of the Korean SMEs leader-senior managers which is combined with paternalistic leadership and proactive, systematic procedures for crisis management in COVID-19, as well as several factors to explain why this leadership emerged. Therefore, our evidence provides new insight of crisis leadership in SMEs out of the western perspectives and suggests a theoretical proposition of crisis leadership in South Korea SMEs.